Geotechnical Evaluation of Landslide in Nanggerang Village - Tan, Yohanes; Zakaria, Zufialdi; Ismawan, Ismawan; Sophian, Irvan; khoirullah, Nur (Faculty of Geological Engineering, Universitas Padjadjaran, 2024)
Landslides are significant geological events that can cause extensive damage to infrastructure, disrupt communities, and pose serious safety hazards. Understanding the mechanisms behind slope failures is crucial for effective risk mitigation and the development of engineering solutions to improve slope stability. According to data from the National Disaster Management Agency (BNPB), Indonesia experienced 83 landslide events from January to February 2024. A notable landslide occurred in Nanggerang Village, Sukasari Sub-district, Sumedang Regency, West Java Province, on February 3, 2024. This landslide happened in a terraced rice field area following heavy rainfall earlier in the day. This study focuses on evaluating the failed slope to understand its condition just before failure and the material properties that influence the landslide event. The research methodology includes field data collection, soil testing, and slope stability analysis using the Limit Equilibrium Method (LEM) with a probabilistic approach via Slide 2 software. The analysis revealed that the failed slope had an average safety factor (FS) of 0.968 and a landslide probability of 58.897%. Sensitivity analysis showed that the cohesion parameter in the soil layer (CWZ) significantly impacts the safety factor of the slope. The study concludes that the reduction in soil cohesion and internal friction angle due to excessive moisture was the primary cause of the landslide, and the cohesion parameter of the soil layer is the most sensitive factor affecting slope stability.